ASSURE MODEL WITH ICT-ENVIRONMENTAL SCIENTIFIC APPROACH TO IMPROVE CRITICAL THINKING ABILITY (Universitas PGRI Sumatera Barat, 2021)
This research is compiling and describing, among others; 1) The background of the development of the Assure model, 2) the main concept of the Assure model, 3) the concept of the Assure model with a scientific approach, ICT-Environment, 4) How to integrate the Assure model with a scientific approach, ICT-environment into the lesson plans. 5) the concept of critical thinking, 6) Description of the application of the Assure model with a scientific approach, ICT-environment to improve critical thinking skills in chemistry learning. Using the literature study methodology. The research finding is that the Assure model can be integrated with a scientific approach and then combined with Information Communication and Technology (ICT) which uses concrete examples from the environment to improve critical thinking skills in chemistry learning. In conclusion, the application of the Assure Model using a scientific approach -ICT - environment will provide effective learning for students to explore chemistry more broadly so as to increase critical thinking power.Keywords : Assure model, quality culture development, critical thinking